2017
DOI: 10.1007/s00405-017-4590-z
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, culture optimization and functional characterization of stem cell neurospheres from mouse neonatal olfactory bulb and epithelium

Abstract: The olfactory epithelium contains basal cells with stem cell characteristics, which have the capacity to differentiate throughout life into olfactory receptor neurons (ORNs). Here we investigate the in vitro characteristics of stem cells taken from the olfactory bulb (OB) and the olfactory epithelium (OE) of neonatal TIS21 knock-in mice. The major aim of the study was the generation of olfactory neurospheres (ONS) derived from OB and OE of neonatal mice as a tool to further analyze the elementary processes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…There is strong evidence that N-Methyl-D-Aspartate (NMDA) receptors play a major role in the central sensitization processes associated with hyperalgesia. 10 Recent animal 8 , 11 and human studies 12 , 13 , 14 , 15 , 16 confirmed this hypothesis, providing evidence that blocking NMDA receptors can prevent opioid-induced hyperalgesia. Studies by Guntz et al 21 showed remifentanil has no direct effect on NMDA receptors but increases NMDA current mediated by μ-opioid receptor activation, probably through an intracellular pathway.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…There is strong evidence that N-Methyl-D-Aspartate (NMDA) receptors play a major role in the central sensitization processes associated with hyperalgesia. 10 Recent animal 8 , 11 and human studies 12 , 13 , 14 , 15 , 16 confirmed this hypothesis, providing evidence that blocking NMDA receptors can prevent opioid-induced hyperalgesia. Studies by Guntz et al 21 showed remifentanil has no direct effect on NMDA receptors but increases NMDA current mediated by μ-opioid receptor activation, probably through an intracellular pathway.…”
Section: Discussionmentioning
confidence: 85%
“…The collapsed cells were suspended with fresh medium (Neurobasal medium, FBS 10%, B27 2%, and antibiotic 0.01%) and then the cells were seeded in 24-well plates (Corning, USA). The plate was stored in an incubator (5% CO 2 ; 37 °C) 13 , 14 ( Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, it is necessary to extract the nervous tissue, in this case the brain, and secondly the region of interest, which may be SVZ or SGZ. Then, the tissue needs to be dissociated enzymatically using enzymes such as trypsin/EDTA, papain, accutase and collagenase, followed by mechanical dissociation [11,34,35]. The cell pellet generated is cultivated on non-adherent substrate using a serum-free growth medium with mitogenic growth factors in a humidified incubator at 37 °C and 5% CO 2 [11].…”
Section: Neurosphere Assaymentioning
confidence: 99%
“…Cerebellum cell cultures were obtained from the department of medical pharmacology of the Ataturk University (Erzurum, Turkey). Briefly, the cells after being centrifuged in 1200 rpm for 5 min were sown in 24 well plate (Corning, USA) by fresh medium (Neurobasal medium, FBS %10, B27 %2 and antibiotic %0,01) and stored at incubator (5% CO 2 ; 37°C) [11,12] (Figure 1).…”
Section: In Vitro Studies Cell Culturesmentioning
confidence: 99%